Sistem Inferensi Fuzzy Tsukamoto Untuk Menentukan Tingkat Kualitas Air Pada Kolam Budidaya Ikan Lele - Muhammad Yudi Abdul Syawari; Hartono (Sienna, 2024)
This study explores the position of catfish as a major aquaculture commodity in Indonesia. In 2013, Indonesia dominated global catfish production with a market share of 75.6%. Despite the higher growth rate of catfish farming compared to other commodities, production did not meet the set targets. The government is working to strengthen national catfish production and enhance its role as a leading commodity in Indonesia. The advantages of catfish lie in its content of leucine and lysine, which are important for children's growth and nitrogen balance. Environmental factors such as freshwater pH (6.5-8.6), optimal temperature (23-30°C), oxygen levels (2-5 mg/L), and ammonia levels (5-7 mg/L) affect the water quality in catfish farming ponds. Natural and human factors such as extreme weather and overfeeding can impact the living conditions and growth of catfish. This study aims to investigate the relationship between pond water quality and catfish growth. The methods used include confusion matrix and Tsukamoto fuzzy logic to determine the accuracy of the water quality assessment system. The main objective of this research is to provide solutions and benefits for the community or the field of study.